El prado del Tio Pedro - Puncel, Maria; Puebla, Teo. (Madrid : Ediciones S.M. : Distribuidor exclusivo, CESMA S.A., 1983)
Uncle Peter has left a meadow and nine sheep to his three sons and their wives. Everybody is happy until one of the wives comes up with an ambitious idea with disastrous results. The reader can choose from three different endings to the story.
"Premio Nacional de Ilustracion Infantil 1982."